2020
DOI: 10.22460/infinity.v10i1.p31-40
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Mathematical Thinking Skill Viewed From Curiosity Through Problem-Based Learning Model on Integral Calculus

Abstract: This study aims to find out the improvement of students’ mathematical critical thinking viewed from curiosity through teaching materials with Problem Based Learning model. This is quasi-experimental research. The samples are, where the overall population consists of 75 samples divided into two classes.  This research employed a simple random sampling technique.  The instruments were the mathematical critical thinking skill test and curiosity questionnaire. The technique of data collection was carried out with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Furthermore, Figure 4 also shows that there were 3 literatures that its PBL treatment duration was more than 3 months and less than or equals 6 months. These literatures reported that PBL had a strong effect on students' MCTS (Happy & Widjajanti, 2014;Zetriuslita et al, 2017;Zetriuslita & Ariawan, 2021), in which the overall its effect size was g = 1,444. Moreover, the significance value of its Z test was less than 0,05.…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, Figure 4 also shows that there were 3 literatures that its PBL treatment duration was more than 3 months and less than or equals 6 months. These literatures reported that PBL had a strong effect on students' MCTS (Happy & Widjajanti, 2014;Zetriuslita et al, 2017;Zetriuslita & Ariawan, 2021), in which the overall its effect size was g = 1,444. Moreover, the significance value of its Z test was less than 0,05.…”
Section: Figurementioning
confidence: 98%
“…Some theoretical evidence in various literature (e.g., Hmelo-Silver (2004), Othman et al (2013), Savery (2006), Torp & Sage (2002), Yew & Goh (2016)) revealed that PBL could facilitate students in developing their MCTS through the design of its phases supporting them to think critically. Some empirical studies related to the PBL implementation for students' MCTS showed that PBL had a strong positive effect on students' MCTS (Ahdhianto et al, 2020;Buana et al, 2020;Ramadhani et al, 2020;Umar et al, 2020;Zetriuslita et al, 2017;Zetriuslita & Ariawan, 2021). Other empirical studies also showed that PBL had a moderate positive effect on students' MCTS (Arviana et al, 2018;Apriliana et al, 2019;Ayuni et al, 2021;Darhim et al, 2020;Haerani et al, 2019;Prihono & Khasanah, 2020;Yolanda, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus students feel confident that mathematics can be understood, thought about, proven, and can be evaluated. Based on the description previously explained, it can be concluded that students' mathematical reasoning ability is the ability or ability of students to solve the problems given (Zetriuslita & Ariawan, 2020).…”
Section: A Introductionmentioning
confidence: 99%
“…Dalam penelitian yang dilakukan oleh Kharisma dan Asman diperoleh informasi bahwa: (1) soal pemecahan masalah tidak semua ada di soal matematika; (2) kemampuan pemecahan masalah matematik peserta didik masih lemah; (3) proses pembelajaran belum memadai untuk membimbing dan melatih peserta didik agar mampu memecahkan masalah (Kharisma & Asman, 2018). Masalah yang terjadi ialah peserta didik enggan untuk mencari jawaban atas soal yang diberikan, mereka tidak mencoba bertanya kepada guru tentang masalah yang tidak mereka pahami hal ini akan mempengaruhi aktivitas siswa dalam belajar (Zetriuslita & Ariawan, 2020).…”
unclassified